Mutant KRAS drives immune evasion by sensitizing cytotoxic T-cells to activation-induced cell death in colorectal cancer - Liu, Huashan; Liang, Zhenxing; Cheng, Sijing; Huang, Liang; Li, Wenxin; Zhou, Chi; Zheng, Xiaobin; Li, Shujuan; Zeng, Ziwei; Kang, Liang (Advanced science, 2023)
The roles of oncogenic KRAS in tumor immune evasion remain poorly understood. Here, mutant KRAS is identified as a key driver of tumor immune evasion in colorectal cancer (CRC). In human CRC specimens, a significant reduction in cytotoxic CD8+ T-cell tumor infiltration is found in patients with mutant versus wild type KRAS. This phenomenon is confirmed by preclinical models of CRC, and further study showed KRAS mutant tumors exhibited poor response to anti-PD-1 and adoptive T-cell therapies. Mechanistic analysis revealed lactic acid derived from mutant KRAS-expressing tumor cells sensitized tumor-specific cytotoxic CD8+ T-cells to activation-induced cell death via NF-κB inactivation; this may underlie the inverse association between intratumoral cytotoxic CD8+ T-cells and KRAS mutation. Importantly, KRAS mutated tumor resistance to immunotherapies can be overcome by inhibiting KRAS or blocking lactic acid production. Together, this work suggests the KRAS-mediated immune program is an exploitable therapeutic approach for the treatment of patients with KRAS mutant CRC.
Gesehen am 31.01.2024